IMPLEMENTATION OF COMPETENCY BASED CURRICULUM (KBK) IN MORAL AND HUMANITARIAN PRINCIPLES: CASE STUDY OF MIFTAHUL HUDA ISLAMIC BOARDING SCHOOL GADING MALANG - Amboro, Kamas Wahyu; Sarofi, Lukman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to explore implementation Competency Based Curriculum (KBK) at Miftahul Huda Islamic Boarding School Gading Malang as a model of integration between traditional Islamic boarding school education and the CBC principles in forming students who have a balance between academic, spiritual, moral and social competencies. This research was conducted using a qualitative approach that focused on exploring the meaning and understanding of the application of CBC in the context of Islamic boarding school education. Data was collected through documentation methods, interviews, and data analysis was carried out using the Miles and Huberman model, with stages of reduction, presentation, and drawing conclusions.The research results show that the Miftahul Huda Gading Islamic Boarding School has succeeded in integrating traditional education with KBK to create inclusive and holistic education. KBK is implemented through three levels of education, namely Ula (basic), Wustho (intermediate), and Ulya (advanced), with each level having a different competency focus. The KBK implementation strategy includes a clear understanding of objectives, various learning methods such as bandongan, sorogan, and deliberative discussions, as well as a student-centred approach. The assessment is carried out using authentic methods that focus on real practice, such as memorization, congregational prayers, and involvement in spiritual activities.The findings also show that the role of teachers as facilitators, parental support, and alumni involvement have an important role in the successful implementation of this KBK. Through implementing this strategy, the Miftahul Huda Gading Islamic Boarding School is able to create an educational environment that supports the development of students' overall competency while maintaining local characteristics and spiritual values in their education. This research recommends that the application of KBK can be an effective model for combining formal education with traditional Islamic boarding school approaches in facing educational challenges in the future.